Ethnic, socio‐economic and geographic inequities in maternal health service coverage in Australia. (16th July 2021) - Fox, Haylee; Topp, Stephanie M.; Lindsay, Daniel; Callander, Emily
Abstract: Background: Disparities in health service use exist in many sectors of Australia's health system, particularly affecting the most vulnerable people in the population, who are typically those with the greatest healthcare needs. Understanding patterns of health service coverage is critical for acknowledging the underlying, systemic drivers including racialised practices that inhibit the uptake of health services for certain population groups. This study aims to determine whether there are disparities in health service utilisation between socioeconomic, geographic and ethnic groups of mothers who experience hypertension, diabetes and mental health conditions. Methods: This study utilised a linked administrative healthcare dataset containing data of all mothers who gave birth in Queensland, Australia, between 2012 and 2015 ( n  = 186, 789), plus their resultant babies ( n  = 189, 909). The study compared health service utilisation for mothers with maternal health conditions between population groups. Results: The results of this study showed a broad trend of inequitable health service utilisation, with mothers who experienced the greatest healthcare needs—First Nations, rural and remote and socio‐economically disadvantaged mothers—being less likely to access health services and in some cases when care was accessed, fewer services being utilised during the perinatal period. Conclusion: Access to health care during the perinatal period is a reflection of Australia's general health system strengths and weaknesses, in particular a failure of the government to translate national and state policy intent into acceptable and accessible care in rural and remote areas, for First Nations women and for mothers experiencing socio‐economic disadvantage.